Relationship between organizational culture, job satisfaction, and performance among health care workers in Querétaro, Mexico - Baltazar-Gómez, Desiree Yvonne (Universidad de Sonora, 2022)
Introduction: The integration of multidisciplinary teams in first level health care organizations, where nurses, physicians, dentists, and administrative personnel are present, is not only to provide quality services, but also to have healthy working conditions. Objective: To determine the relationship between organizational culture and job satisfaction with the performance of health care workers. Methodology: Correlational and analytical study. This study was performed in 125 workers selected using probabilistic sampling, and it was requested to answer this survey voluntarily, under informed consent; workers with six months of seniority were excluded. The instrument consisted of organizational culture, job satisfaction and job performance; data processing was made using SPSS version 25; Pearson's R was used due to the normal distribution of the data. Authorization was obtained from the bioethics and research committees. Results: Organizational culture showed 71% of medium level of consistency and 67% of adaptability. Both job satisfaction in motivation showed 98% and satisfaction showed 96%, obtaining a medium level. Job performance was high. In organizational culture and job performance, there was an association in adaptability with interpersonal relationships and quality, p=0.01, consistency with quality and interpersonal relationships, p=0.01. In job satisfaction and job performance, there was association in mission with quality and satisfaction with teamwork, p=0.05. Conclusions: A significant statistical correlation was seen between the variables, generating assertive integration strategies, recognizing their experience, providing conditions for their professional development, and within the health institution influencing job performance and the quality of service provided.